Different Aspects of Pre-schoolers` Movement Development - Augstkalne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
the psychical, physical and mental development of a pre-school pupil, cognition process of the surrounding world, improvement of body’s functional abilities and development of physical characteristics is only possible through child’s physical activity. In order for the child to be active, he/she needs to learn the basic movements essential for life. By learning these movements and the methods or techniques of their executions the movement experience of the child is enriched. And this movement experience is necessary for various situations in life as well as for independent functioning. Promotion of movements and activities in preschool is linked with the entire pedagogical process that is being realized during the whole day.